Ruthenium oxychloride supported by manganese oxide for stable oxygen evolution in acidic media. Issue 39 (15th September 2022) - Zhao, Yunxing; Hu, Jun; Chiang, Chao-Lung; Li, Ying; Yang, Weichuang; Yang, Zhenhai; Hung, Wei-Hsuan; Lin, Yan-Gu; Chen, Zhong; Li, Bin; Gao, Pingqi; Li, Hong
Abstract : A stabilization strategy is developed by dispersing ruthenium oxychloride into a manganese oxide supporting material, which greatly enhances the catalytic stability of a ruthenium-based catalyst for oxygen evolution reaction under acidic conditions. Abstract : Despite the recent advances in enhancing the durability and reducing the overpotential of ruthenium (Ru)-based electrocatalysts for acidic oxygen evolution reaction (OER), their stability hardly meets the requirement of practical application. Moreover, a cost-effective strategy to stabilize the highly active but unstable Ru species is desirable. Herein, we report a stable electrocatalyst for acidic OER by dispersing the Ru oxychloride active species into a manganese oxide support (RuOCl@MnO x ) to form highly dispersed Ru–O–Mn without the alteration of vibrational modes and bond parameters of the MnO6 group, as suggested by Raman and synchrotron radiation characterization studies. The catalyst is stable for continuous operation over 280 h with an overpotential of 228 mV at 10 mA cm −2 and over 200 h at 100 mA cm −2, among the most stable low-mass-loading Ru-based OER electrocatalysts in acidic media. Complementary theoretical calculations ascribe the excellent stability to its high oxidation potential and low formation/surface energies, consistent with experimental observations. The enhanced activity is attributed to the four-coordinated Ru site that bears a low overpotential determined by the formation of O* from OH*. Our work thus offers a new strategy for synthesizing robust OER electrocatalysts of PEM electrolyzers with superior activity.